Analysis of the Hydrodynamic Characteristics of Limboto Lake Waters Based on Momentum Fluxes - Mikail Gabriel Khan Khan; Raghel Yunginger Yunginger; Dewa Gede Eka Setiawan; Mohamad Jahja; Icha Untari Meidji; Haerul Ahmadi; Cucu Kusmayancu; Merpati Teodoris Nalle (Departement of Physics Faculty of Mathematics and Natural Sciences, and Institute of Research and Community Services Udayana University, Kampus Bukit Jimbaran Badung Bali, 2026)
The waters of Lake Limboto show a decline in water quality, characterized by a decrease in clarity. Environmental factors, such as wind speed and direction, play a significant role in influencing the dynamics and quality of lake waters. To understand the influence of wind on water conditions, a comprehensive hydrodynamic study is required. This study focuses on analyzing the hydrodynamic characteristics of Lake Limboto waters based on momentum flux and its implications for lake water conditions. Wind speed and direction measurements were conducted on seven ducks in Lake Limboto waters during the period of November 1-3, 2024. Data were collected in the morning, afternoon, and evening. The lake's hydrodynamic characteristics were determined using formulas from the measured data. Hydrodynamic characteristics were interpolated using IDW cross validation leave one out and optimized with rank and neighboring point parameters. Wind direction was interpolated using IDW and converted into a vector field using Vector Field Layer Manager. It was found that the momentum flux by wind in Lake Limboto waters has a value range of 0-0.05 N/m2, and cross validation produced an RMSE of 0.003-0.01 N/m2. The interaction of momentum flux from wind and river flow causes sediment to be deposited in the coastal area of ​​Lake Limboto.